Current understanding on Villosiclava virens, a unique flower‐infecting fungus causing rice false smut disease. (13th April 2016) - Fan, Jing; Yang, Juan; Wang, Yu‐Qiu; Li, Guo‐Bang; Li, Yan; Huang, Fu; Wang, Wen‐Ming
Summary: Villosiclava virens (Vv) is an ascomycete fungal pathogen that causes false smut disease in rice. Recent reports have revealed some interesting aspects of the enigmatic pathogen to address the question of why it specifically infects rice flowers and converts a grain into a false smut ball. Comparative and functional genomics have suggested specific adaptation of Vv in the colonization of rice flowers. Anatomical studies have disclosed that Vv specifically infects rice stamen filaments before heading and intercepts seed formation. In addition, Vv can occupy the whole inner space of a spikelet embracing all floral organs and activate the rice grain‐filling network, presumably for nutrient acquisition to support the development of the false smut ball. This profile provides a general overview of the rice false smut pathogen, and summarizes advances in the Vv life cycle, genomics and genetics, and the molecular Vv–rice interaction. Current understandings of the Vv–rice pathosystem indicate that it is a unique and interesting system which can enrich the study of plant–pathogen interactions. Taxonomy: Ustilaginoidea virens is the anamorph form of the pathogen (Kingdom Fungi; Phylum Ascomycota; Class Ascomycetes; Subclass Incertae sedis; Order Incertae sedis; Family Incertae sedis; Genus Ustilaginoidea ). The teleomorph form is Villosiclava virens (Kingdom Fungi; Phylum Ascomycota; Class Ascomycetes; Subclass Sordariomycetes; Order Hypocreales; Family Clavicipitaceae; Genus Villosiclava ). Disease symptoms: The only visible symptom is the replacement of rice grains by ball‐shaped fungal mycelia, namely false smut balls. When maturing, the false smut ball is covered with powdery chlamydospores, and the colour changes to yellowish, yellowish orange, green, olive green and, finally, to greenish black. Sclerotia are often formed on the false smut balls in autumn. Identification and detection: Vv conidia are round to elliptical, measuring 3–5 μm in diameter. Chlamydospores are ornamented with prominent irregularly curved spines, which are 200–500 nm in length. The sclerotia are black, horseshoe‐shaped and irregular oblong or flat, ranging from 2 to 20 mm. Nested polymerase chain reaction (PCR) and quantitative PCR have been developed to specifically detect Vv presence in rice tissues and other biotic and abiotic samples in fields. Host range: Rice is the primary host for Vv. Natural infection by Vv has been found on several paddy field weeds, including Digitaria marginata, Panicum trypheron, Echinochloa crusgalli and Imperata cylindrica . However, the occurrence of infection in these potential alternative hosts is very rare. Life cycle: Vv infects rice spikelets at the late rice booting stage, and produces false smut balls covered with dark‐green chlamydospores. Occasionally, sclerotia form on the surface of false smut balls in late autumn when the temperature fluctuates greatly between day and night. Both chlamydospores and sclerotia may serve as primary infection sources. Rainfall at the rice booting stage is a major environmental factor resulting in epidemics of rice false smut disease. Disease control: The use of fungicides is the major approach for the control of Vv. Several fungicides, such as cuproxat SC, copper oxychloride, tebuconazole, propiconazole, difenoconazole and validamycin, are often applied. However, the employment of resistant rice cultivars and genes has been limited, because of the poor understanding of rice resistance to Vv. Useful websites: Villosiclava virens genome sequence:http://www.ncbi.nlm.nih.gov/Traces/wgs/?val=JHTR01#contigs